2019
DOI: 10.1080/1051712x.2019.1603354
|View full text |Cite
|
Sign up to set email alerts
|

The brand personality dimensions of business-to-business firms: a content analysis of employer reviews on social media

Abstract: Purpose: The purpose of this paper is to explore the brand personalities that employees are creating of their employer brands, in particular business-to-business (B-to-B) brands, when describing these brands on social media. We examine how the brand personalities, based on written online reviews, differ between high-and low-ranked, and high-and low-rated brands. Methodology/Approach: 6,300 written employee reviews from a social media platform, Glassdoor, are used for content analysis in DICTION, to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 85 publications
(116 reference statements)
0
17
0
Order By: Relevance
“…As mentioned, the different employer rating scales reflect different facets of EVP. Although all EVP facets are promising, these different types of EVP do not matter to the same extent for internal employees [35]. In other words, different specific employer ratings (culture and values, work-life balance, senior management, compensation and benefits, career opportunity, CEO endorsement, and business outlook) have different weights in predicting or explaining the overall employer rating, which, in turn, allows employers to rank them in order of importance and priority; otherwise, employers may suffer from waste of resources on noncritical EVP facets [13].…”
Section: Specific Employer Ratings and Overall Employer Ratings Throumentioning
confidence: 99%
“…As mentioned, the different employer rating scales reflect different facets of EVP. Although all EVP facets are promising, these different types of EVP do not matter to the same extent for internal employees [35]. In other words, different specific employer ratings (culture and values, work-life balance, senior management, compensation and benefits, career opportunity, CEO endorsement, and business outlook) have different weights in predicting or explaining the overall employer rating, which, in turn, allows employers to rank them in order of importance and priority; otherwise, employers may suffer from waste of resources on noncritical EVP facets [13].…”
Section: Specific Employer Ratings and Overall Employer Ratings Throumentioning
confidence: 99%
“…They demonstrated that top-ranked (vs. low ranked) employers are perceived as less exciting, rugged, and sincere. Furthermore, high (vs. low) rated (one vs. five stars) reviews displayed more competence, excitement, sincerity, sophistication, but less ruggedness [36].…”
Section: Othermentioning
confidence: 93%
“…They showed that lower ratings increase audit fees, audit report lag length, and firms' likelihood of receiving modified going concern opinions [20]. Third, Robertson et al compared brand personality perceptions between reviews of highly and lowly ranked firms according to Brandwatch's B2Branking and between highly and lowly rated reviews (according to reviews' overall rating) [36]. They demonstrated that top-ranked (vs. low ranked) employers are perceived as less exciting, rugged, and sincere.…”
Section: Othermentioning
confidence: 99%
See 2 more Smart Citations